Sheldon Wolin’s (In)Vocations: Dichotomies, Paradoxes, and the Mystery of Politics - Vega, Facundo (Araucaria, 2016)
Sheldon Wolin, one of the most influential contemporary political theorists, died in 2015 at the age of 93. His remarkable legacy within political thought includes written works such as Politics and Vision and lives on as well in a variety of his former students, for instance, Cornel West and Wendy Brown. Wolin’s intellectual heritage is sure to persist, given that he "lived in the presence of time past, time present, and time future".This brief essay, however, does not seek an obituary tone. Rather, I will comment on particular topics inherent to Wolin’s interpretation of democracy by taking into consideration Bonnie Honig’s twofold rendition of it, centered on the paradoxical character of politics.